(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article analyzes common linguistic challenges faced by medical students in English, focusing on grammatical, lexical, and communicative errors in academic and clinical contexts. It also proposes effective remedial strategies to enhance students’ language competence for professional and educational purposes.